Late complications of scleral buckles in the orbit - Juan Edric González Mondragón; Adriana Davila-Camargo (The Pan-American Journal of Ophthalmology, 2023)
A scleral buckle is a surgical procedure used for rhegmatogenous retinal detachment repair. Different materials have been used for this technique over the years. During the 1980s, MIRAgel (MIRA Inc., Waltham, Mass) introduced hydrogel bands. This material allowed easy handling for the surgeon and self-expansion over time. A decade after their introduction, late complication reports began to appear, associated with uncontrolled expansion and the need for surgical removal. We present two complete cases and a literature review of patients presenting with ophthalmoplegia, pain, and proptosis, 25 years after hydrogel scleral buckle surgeries.